Implikasi Islamic-Kaizen di Lembaga Keuangan Syariah (LKS) agar Tercapainya Maqashid al-Syariah (In Press) - Miswanto; Iza Hanifuddin (Jurnal Iqtisaduna, 2023)
Abstract, The industrial era 4.0 has changed to the era of society 5.0. It requires all aspects of life to change with the era of its time. Whether you want it or not, Islamic Financial Institutions (LKS) in Indonesia must also adjust to the growing era. The purpose of this study is to determine the concept of islamic-kaizen and the extent of the implications of islamic-kaizen in Islamic Financial Institutions in order to achieve maqashid al-syairah in order to answer the challenges of changing times. Kaizen is often referred to and used in the manufacturing industry but is rarely referred to and used in Islamic Financial Institutions. Kaizen derived from Japanese culture is analyzed and applied in Financial Institutions used for improvement in a better direction according to islamic sharia. Using a qualitative approach, data collection techniques are carried out in a combined or triangulation manner and then the results are expected to emphasize meaning more than generalization. The data collected using library research with the main data taken from the Indonesian Sharia Banking Financial Statements (LKPSI) from 2018 to 2021 from the Financial Services Authority (OJK) and supported by secondary data from books, journals and the internet, problems related to Islamic Financial Institutions (LKS) were found. With the concept of islamic-kaizen the problem is analyzed its implications in Islamic Financial Institutions. From this research, it is concluded that Islamic-kaizen will affect Islamic Financial Institutions if carried out continuously and become a culture based on the main objectives of Shari'a (maqashid al-syariah) so that prosperity can be achieved.